2020
DOI: 10.1021/acsomega.0c02374
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Statistical Investigation of Reservoir Properties with the Effect of Waterflooding Treatment

Abstract: An oilfield reservoir over long-term operation may have different petrophysical information, which has a significant impact on oilfield maintenance and finance. Successful oilfield enhanced oil recovery benefits a lot from identifying and analyzing the variations of the critical properties after long-term waterflooding treatments. Since the inspection wells drilled within different development periods contain the core samples that have the petrophysical information at that period, it is necessary to collect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Thus, using the same concept as in Figure 7, dependencies can be built to predict the change in effective permeability by class. Analysing Figure 7, it can be concluded that as the water saturation of the rock samples increases from 0 to 54.0 %, their effective gas permeability will decrease under both standard and reservoir conditions and therefore there will be a transition from higher to lower permeability classes [37]. In fairness, it should be noted that this graph reflects the influence not only of residual water saturation, but also of porosity and structure of the pore space on permeability.…”
Section: Figurementioning
confidence: 91%
“…Thus, using the same concept as in Figure 7, dependencies can be built to predict the change in effective permeability by class. Analysing Figure 7, it can be concluded that as the water saturation of the rock samples increases from 0 to 54.0 %, their effective gas permeability will decrease under both standard and reservoir conditions and therefore there will be a transition from higher to lower permeability classes [37]. In fairness, it should be noted that this graph reflects the influence not only of residual water saturation, but also of porosity and structure of the pore space on permeability.…”
Section: Figurementioning
confidence: 91%
“…The statistical method is to analyze small seismic windows within the reservoir [2], [10], [11], [14], [34], [35]. The studied seismic sections (Fig.…”
Section: Statistical Characterization Of Real Seismic Tracesmentioning
confidence: 99%
“…First, we tested the discriminatory power of the variables by using only one family at a time [7], [8], [34], [35]. The 19 variables calculated from the autocorrelation amplitude spectrum allow some grouping of individuals according to their facies, but the barycenter of the classes is less close.…”
Section: Discriminant Analysis Of Seismic Traces Of Different Seismic...mentioning
confidence: 99%
“…These fines are generally held within the formation water film that surrounds the quartz grain in water-wet conditions . Fine migration may happen in different types of natural and technical processes, such as water aquifer recharging by some external water source, underground formation water disposal, groundwater flows, and invasion of drilling muds, invasion of completion fluids, acidizing and waterflooding treatments, high rate oil and gas production and injection, and improper design of oil recovery processes with low-salinity water injection. …”
Section: Introductionmentioning
confidence: 99%